2022
DOI: 10.53713/nhs.v2i3.129
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Gadget Usage and Adolescents Eye Health

Abstract: The changes in public life style cause the raising demand in practical communication media. The data from a survey conducted in 2014 in United States shows that the gadgets ownership in group of people ranged from 13 to 15 years old has increased from 35% to 55%, and tablet ownership has increased twice as much, from 18% to 37%. Referring to the previous study, it is said that teenagers are susceptible to experience the negative effect from the excessive use of gadget, for the gadget screen exposure could indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Remaja rentan mengalami efek negatif dari penggunaan gadget yang berlebihan, karena paparan layar gadget dapat memicu pelepasan hormon dopamin yang berperan penting dalam membentuk sifat adiktif. Penelitian yang dilakukan oleh Ariyanti dkk pada tahun 2022 mendapatkan hasil bahwa terdapat hubungan yang positif dan signifikan antara penggunaan gadget dengan kesehatan mata remaja 6 .…”
Section: Pendahuluanunclassified
“…Remaja rentan mengalami efek negatif dari penggunaan gadget yang berlebihan, karena paparan layar gadget dapat memicu pelepasan hormon dopamin yang berperan penting dalam membentuk sifat adiktif. Penelitian yang dilakukan oleh Ariyanti dkk pada tahun 2022 mendapatkan hasil bahwa terdapat hubungan yang positif dan signifikan antara penggunaan gadget dengan kesehatan mata remaja 6 .…”
Section: Pendahuluanunclassified
“…Blue light is the emission from the screens of digital devices, such as televisions, laptops, handphones, tablets, and other gadgets. The human eye is generally sensitive to 1 part of the light wave spectrum, namely visible light [10]. Previous studies have shown that prolonged exposure to blue light from digital devices can cause macular degeneration, which is an important part of the eye's retina that, if damaged, can lead to visual impairment [11].…”
Section: Introductionmentioning
confidence: 99%